2020
DOI: 10.1038/s41467-020-17882-2
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy regulates fatty acid availability for oxidative phosphorylation through mitochondria-endoplasmic reticulum contact sites

Abstract: Autophagy has been associated with oncogenesis with one of its emerging key functions being its contribution to the metabolism of tumors. Therefore, deciphering the mechanisms of how autophagy supports tumor cell metabolism is essential. Here, we demonstrate that the inhibition of autophagy induces an accumulation of lipid droplets (LD) due to a decrease in fatty acid β-oxidation, that leads to a reduction of oxidative phosphorylation (OxPHOS) in acute myeloid leukemia (AML), but not in normal cells. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(89 citation statements)
references
References 58 publications
(68 reference statements)
3
86
0
Order By: Relevance
“…Lipophagy was first shown to be an active way to get energy under starvation [102] through the association of autophagic components with lipid droplets (LDs). Recently, lipophagy has been demonstrated to regulate the fatty acid availability for the β-oxidation through contact sites between the mitochondria and the ER [103]. Regarding virus-associated hijacking of the cell lipid metabolism, Heaton and Randall [100] early showed that increased β-oxidation and the depletion of triglycerides was concurrent with and necessary for DENV replication.…”
Section: Lipid-related Host Factors Associated To the Rcs' Buildupmentioning
confidence: 99%
“…Lipophagy was first shown to be an active way to get energy under starvation [102] through the association of autophagic components with lipid droplets (LDs). Recently, lipophagy has been demonstrated to regulate the fatty acid availability for the β-oxidation through contact sites between the mitochondria and the ER [103]. Regarding virus-associated hijacking of the cell lipid metabolism, Heaton and Randall [100] early showed that increased β-oxidation and the depletion of triglycerides was concurrent with and necessary for DENV replication.…”
Section: Lipid-related Host Factors Associated To the Rcs' Buildupmentioning
confidence: 99%
“…Considering that TRMT61B downregulation diminishes the expression of various protein components of at least complex I and IV, an indirect link between TRMT61B and autophagy can be proposed. Nevertheless, we cannot exclude the possibility that autophagy was a direct TRMT61B target whose inhibition could have a negative impact on mitochondrial metabolism, as it has been recently reported in acute myeloid leukemia 92 . Consequently, a complex network of interactions might be simultaneously working in a TRMT61B dependent manner and being influenced each other.…”
Section: Discussionmentioning
confidence: 87%
“…Autophagy is also activated after glutamate depletion and protects cancer cells from impairment of energy production through upregulation of lipid catabolism [ 139 ]. In addition, blockage of autophagic flux decreases OXPHOS, leading to lipid accumulation and cell growth arrest in acute myeloid leukemia, revealing an unquestionable linkage between autophagy and FAO levels in cancer cells [ 140 ]. It is notable that autophagy activation is also accompanied by increased intracellular lipid reservation in certain contexts.…”
Section: Autophagic Regulation: a Potential Mechanism For Cancer Cmentioning
confidence: 99%